The Dilemma of Language Ethics and Freedom of Expression in the Use of Language in Social Media : Analysis of the Hate Speech Case - Lira Mey Nisa; Tiodame Layupa Simanullang; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research examines the dilemma between language ethics and freedom of expression in relation to hate speech on social media. A mandatory human right, freedom of expression allows people to express their opinions and encourages democratic society. Its misuse on digital platform, however, frequently leads to hate speech that incites animosity, reinforces assumptions, and insults the dignity of the target audience. This research qualitatively analyzes cases of hate speech and freedom of expression in social media spaces through discourse and content analysis. As a result, this research illustrates the dilemma between the expression of hate speech that violates ethical boundaries and the defense of freedom of expression in a democratic society. It also explores principles to maintain the balance between freedom of expression.